2021
DOI: 10.1371/journal.pgen.1009650
|View full text |Cite
|
Sign up to set email alerts
|

DAF-18/PTEN inhibits germline zygotic gene activation during primordial germ cell quiescence

Abstract: Quiescence, an actively-maintained reversible state of cell cycle arrest, is not well understood. PTEN is one of the most frequently lost tumor suppressors in human cancers and regulates quiescence of stem cells and cancer cells. The sole PTEN ortholog in Caenorhabditis elegans is daf-18. In a C. elegans loss-of-function mutant for daf-18, primordial germ cells (PGCs) divide inappropriately in L1 larvae hatched into starvation conditions, in a TOR-dependent manner. Here, we further investigated the role of daf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…We analyzed a putative null mutant, cec-4(ok314), shown by Belew et al to disrupt PGC chromatin compaction. We found that the mutant PGCs do not proliferate during L1 starvation (data not shown), suggesting that transcriptional activation is not sufficient for PGC proliferation, though it is necessary ( Fry et al, 2021 ). However, the mutant has reduced brood size overall, and the effect is particularly pronounced following 8 days of L1 starvation ( Figure 7A ), revealing a significant consequence of transcriptional activation in starved PGCs.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…We analyzed a putative null mutant, cec-4(ok314), shown by Belew et al to disrupt PGC chromatin compaction. We found that the mutant PGCs do not proliferate during L1 starvation (data not shown), suggesting that transcriptional activation is not sufficient for PGC proliferation, though it is necessary ( Fry et al, 2021 ). However, the mutant has reduced brood size overall, and the effect is particularly pronounced following 8 days of L1 starvation ( Figure 7A ), revealing a significant consequence of transcriptional activation in starved PGCs.…”
Section: Resultsmentioning
confidence: 94%
“…Three of our six largest clusters (clusters 2, 4, and 6) are expressed at relatively low levels upon hatching, exhibit peak expression levels beyond 4 days of starvation, and either maintain or increase expression levels up to 12 days of starvation. These clusters are enriched with genes expressed in several tissues related to reproduction, including “germline,” “gonad primordium,” and “reproductive system” ( Figure 3A ) ( Angeles-Albores et al, 2016 ), which was surprising given that transcription is repressed in germ cells in the first few hours of L1 arrest ( Belew et al, 2021 ; Fry et al, 2021 ). We directly assessed if genes typically expressed in the soma or germline exhibit distinct expression patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge about how PGCs are induced comes largely from studies in model mammals, including nonhuman primates, 86 , 87 , 89 95 mice, 12 , 83 , 85 , 96 108 and pigs. 109 – 118 Studies in the other group of model organisms, including chicken, 119 126 zebrafish, 63 , 64 , 66 , 67 , 127 medaka, 128 136 frogs, 55 57 , 137 Drosophila, 138 146 and Caenorhabditis elegans, 147 156 provide abundant information about PGC specification by preformation or maternally inherited determinants. The PGCs in these two groups of organisms show a similarity that is the presence of some kind of aggregate of electron-dense, basophilic bodies containing the proteins and RNAs, (e.g., VASA, NANOS, and MAGO) in their cytoplasm.…”
Section: Precursors For the Gametes: Human Primordial Germ Cellsmentioning
confidence: 99%